A novel ICMetric public key framework for secure communication. (1st December 2021) - Tahir, Ruhma; Tahir, Shahzaib; Tahir, Hasan; McDonald-Maier, Klaus; Howells, Gareth; Sajjad, Ali
Abstract: The Integrated Circuit Metric (ICMetric) technology is a novel trust basis that uses the system features to create an identification of a device. The ICMetric of the device is used for the provision of security services, thereby addressing the issue of trust associated with device identity. The ICMetric technology can be adapted to function with varying environments; however, the short length and low entropy of the ICMetric key pose a major threat to applications based on ICMetric. This paper proposes a secure comprehensive ICMetric based architecture that facilitates asymmetric ICMetric applications for secure services in an end-to-end environment. This novel framework has been designed keeping in mind the construction principles of ICMetric thereby preventing threats that are prevalent in many security schemes. Finally, an empirical evaluation and feasibility has been presented by implementing the proposed framework and doing an extensive security analysis.